Anna Karenina - Tolstoy, Leo (Singapore Penguin Random House, 2024)
Anna Karenina, a beautiful, sensuous, and rebellious young woman, is unhappily married to the wealthy but cold aristocrat Alexey Alexandrovitch. Restless in her passionless marriage, she lives in a society and times where Church rules the order for the wealthy; one wrong can bring down the entire family. Thus, she was floating through life until she met Count Vronsky. They fell passionately in love, convinced they met their soulmates. The story goes through their struggles to get approval for divorce, and their desire to live together in a complex society. Tolstoy uses his characters to raise complex questions about family$1 (Bs, egos that become a handcuff, and a society that becomes limiting to individual happiness. His famous novel is seemingly ahead of its times as it questions the inherent bias within people. s
Keywords: English Fiction; Family Novel